Incorporation of Mo and W into nanostructured BiVO4 films for efficient photoelectrochemical water oxidation - Berglund, Sean P.; Rettie, Alexander J. E.; Hoang, Son; Mullins, C. Buddie (Physical chemistry chemical physics : PCCP, 2012)
Porous, nanostructured BiVO4 films are incorporated with Mo and W by simultaneous evaporation of Bi, V, Mo, and W in vacuum followed by oxidation in air. Synthesis parameters such as the Bi : V : Mo : W atomic ratio and deposition angle are adjusted to optimize the films for photoelectrochemical (PEC) water oxidation. Films synthesized with a Bi : V : Mo : W atomic ratio of 46 : 46 : 6 : 2 (6% Mo, 2% W) demonstrate the best PEC performance with photocurrent densities 10 times higher than for pure BiVO4 and greater than previously reported for Mo and W containing BiVO4. The films consist of a directional, nanocolumnar layer beneath an irregular surface structure. Backside illumination utilizes light scattering off the irregular surface structure resulting in 30-45% higher photocurrent densities than for frontside illumination. To improve the kinetics for water oxidation Pt is photo-deposited onto the surface of the 6% Mo, 2% W BiVO4 films as an electrocatalyst. These films achieve quantum efficiencies of 37% at 1.1 V vs. RHE and 50% at 1.6 V vs. RHE for 450 nm light.